Emergency department presentation for uncomplicated acute rhinosinusitis is associated with poor access to healthcare. (17th March 2015) - Scangas, George A.; Ishman, Stacey L.; Bergmark, Regan W.; Cunningham, Michael J.; Sedaghat, Ahmad R.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Uncomplicated acute rhinosinusitis (ARS) is most appropriately managed in an outpatient clinic setting. Some ARS patients present to emergency departments (EDs) for care. We investigates factors associated with ARS presentation to EDs versus outpatient settings. Study Design Cross‐sectional study. Methods A total of 17, 122, 551 pediatric and adult patient visits from the 2009 and 2010 National Ambulatory Medical Care and National Hospital Ambulatory Medical Care Surveys for ARS were identified. Patients with ARS complications were excluded. Univariate and multivariate associations identified demographic and socioeconomic characteristics of ARS patients independently associated with ED presentation. Temperature >100°F was used as a proxy for ARS severity. Results Patients with Medicaid (odds ratio [OR] = 10.82, P < .001) or no insurance (OR = 9.14, P < .001) more likely presented to EDs when compared to patients with private insurance or Medicare. Independently, black patients (OR = 6.01, P < .001) more likely presented to EDs when compared to white or Hispanic patients. No significant association was seen with metropolitan or socioeconomic status based upon the patients' home zip code. Conclusions Presentation of ARS patients to EDs is associated with health insurance type and patient race independent of socioeconomic status. Healthcare access appears to be a primary determinant of whether patients present to an ED or outpatient setting for this common health problem. The association between race and ED presentation suggests cultural underpinnings requiring further characterization. Reducing barriers to care, for example through broader health insurance coverage, may enhance access to outpatient care providers and decrease costs associated with unnecessary ED presentation. Level of Evidence 4. Laryngoscope, 125:2253–2258, 2015